ASTIKHDAM E-MUFRADAT GAME LITARQIAT QUDRAT ALTALAMIDH EALAA SAYTARAT ALMUFRADAT (DIRASAT TAJRIBIAT LILMARHALAT ALIABTIDAYIYATI) - Amrullah, Amrullah; Hayati, Salma; Wahyuni Hidayanti, Sri (SHAWTUL ARAB, 2025)
This study aims to evaluate the effectiveness of technology-based media, specifically the E-Mufradat Game, in improving the Arabic vocabulary mastery of students at SD Islam Qur'ani Banda Aceh. The research employs a quantitative approach with a quasi-experimental non-equivalent control group design. The subjects of the study consist of two classes: an experimental class using the E-Mufradat Game and a control class without similar treatment, each comprising 15 students. Data collection techniques include pretests and posttests, while data analysis was conducted using SPSS 21 with normality tests, homogeneity tests, and independent sample t-tests. The results of the study show a significant difference in vocabulary mastery between the experimental and control groups. The average post-test score of the experimental group increased to 75.3 compared to the control group, which only reached 33. Hypothesis testing revealed that the use of the E-Mufradat Game significantly enhances vocabulary mastery (p < 0.05). Moreover, this medium also provides a more interactive, enjoyable, and effective learning experience, fostering an active classroom environment. This study supports previous findings that technology-based learning media can enhance student engagement and learning outcomes. Thus, the E-Mufradat Game can serve as an innovative alternative in Arabic language instruction to improve students' vocabulary mastery